The intracellular chloride channel 4 (CLIC4) activates systemic sclerosis fibroblasts. (17th December 2020) - Wasson, Christopher W.; Ross, Rebecca. L.; Morton, Ruth; Mankouri, Jamel; Del Galdo, Francesco
Abstract: Objectives: Tissue fibrosis in SSc is driven by active fibroblasts (myofibroblasts). Previous studies have shown the intracellular chloride channel 4 (CLIC4) mediates the activation of cancer-associated fibroblasts. In this study we investigated the role of CLIC4 in SSc fibroblast activation. Methods: Fibroblasts were obtained from full thickness skin biopsies from SSc patients (early-diffuse). RNA and protein were collected from the fibroblasts and CLIC4 transcript and protein levels were assessed by qPCR and western blot. SSc patient fibroblasts were treated with the chloride channel inhibitors nitro-2-(3-phenylpropylamino)benzoic acid and indyanyloxyacetic acid 94. Results: CLIC4 was expressed at significantly higher levels in SSc patients' fibroblasts compared with healthy controls, at both the transcript (3.7-fold) and protein (1.7-fold) levels. Inhibition of the TGF-β receptor and its downstream transcription factor SMAD3 led to a reduction in CLIC4 expression, confirming this pathway as the main driver of CLIC4 expression. Importantly, treatment of SSc fibroblasts with known pharmacological inhibitors of CLIC4 led to reduced expression of the myofibroblast markers collagen type 1 and α-smooth muscle actin, inferring a direct role for CLIC4 in disease pathogenesis. Conclusions: We have identified a novel role for CLIC4 in SSc myofibroblast activation, which strengthens the similarities of SSc fibroblasts with cancer-associated fibroblasts and highlights this channel as a novel target for therapeutic intervention.